Biopsychosocial model of resilience in young adults with multiple sclerosis (BPS-ARMS): an observational study protocol exploring psychological reactions early after diagnosis. Issue 8 (2nd August 2019) - Gajofatto, Alberto; Donisi, Valeria; Busch, Isolde Martina; Gobbin, Francesca; Butturini, Elena; Calabrese, Massimiliano; Carcereri de Prati, Alessandra; Cesari, Paola; Del Piccolo, Lidia; Donadelli, Massimo; Fabene, Paolo; Fochi, Stefania; et al.
Abstract : Introduction: Multiple sclerosis (MS), the most common neurological disease causing disability in young adults, is widely recognised as a major stress factor. Studies have shown that the first years after the diagnosis are distressing in terms of adjustment to the disease and that MS negatively affects patients' psychological well-being, quality of life (QoL) and social functioning. However, the links between disease-specific variables at diagnosis, resilience and psychological adjustment of patients with MS remain largely unexplored, especially in adolescents and young adults. This observational study aims to fill the gap of knowledge on b iop sychos ocial characteristics and r esilience of young a dults with MS to evaluate the relationship among these variables and to develop a biopsychosocial model of resilience. Methods and analysis: Biological and clinical characteristics of young adults newly diagnosed with MS will be investigated by collecting clinical information, performing neurological examinations, MRI and analysing cerebrospinal fluid and blood biomarkers (eg, measures of inflammation), body composition, gut microbiota and movement/perceptual markers. Psychosocial characteristics (eg, psychological distress, coping strategies), QoL, psychological well-being and resilience will be assessed by self-report questionnaires. Comparative statistics (ie, analysis of variance or unpaired samples t-test, correlation and regression analyses) will be applied to evaluate the relationship among biological, psychological and social factors. The results are expected to allow a comprehensive understanding of the determinants of resilience in young patients with MS and to inform resilience interventions, tailored to young patients' specific needs, aiming to reduce the risk of maladaptive reactions to the disease and to improve psychological well-being and QoL. Ethics and dissemination: The study has been approved by the Verona University Hospital Ethics Committee (approval number: 2029CESC). The findings will be disseminated through scientific publications in peer-reviewed journals, conference presentations, social media and specific websites. Trial registration number: ClinicalTrials.gov (NCT03825055 ).